Developing primary school students' foreign language learner self-concept. (June 2019) - Waddington, Julie
Abstract: The experimental study presented in this paper explores the emergence and development of foreign language learner self-concepts in young learners. The study was conducted in the linguistically rich yet politically complex context of Catalonia, in a rural primary school. Within an action research framework, the study focused on self-efficacy beliefs and learner attributions and set out to address two principal research questions: i) To what do young language learners attribute their self-efficacy in the domain of foreign language learning? ii) How do these attributions affect their foreign language learner self-concept? Results showed strong causal links between learner attributions, self-efficacy levels, and emerging self-concepts. They also highlighted debilitating attributions which may be impeding the emergence of positive foreign language self-concepts. The pedagogical implications of these findings are discussed, as well as the need to distinguish between subject-based self-concept (e.g. language self-concept or mathematics self-concept) and subject-specific learner self-concept. A spectrum of foreign language learner positions is proposed as a pedagogical tool to identify learner positions as a step towards developing positive and situated foreign language learner self-concepts.